2022
DOI: 10.1111/cogs.13186
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the True Cost of Garden Pathing: A Computational Model of Latent Cognitive Processes

Abstract: What is the processing cost of being garden-pathed by a temporary syntactic ambiguity? We argue that comparing average reading times in garden-path versus non-garden-path sentences is not enough to answer this question. Trial-level contaminants such as inattention, the fact that garden pathing may occur non-deterministically in the ambiguous condition, and "triage" (rejecting the sentence without reanalysis; Fodor & Inoue, 2000) lead to systematic underestimates of the true cost of garden pathing. Furthermore,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…They showed that while surprisal correctly predicted that reading times on the boldfaced words in (1a) are longer than the reading times on the same words in (1b), it predicted a much smaller excess processing difficulty on (1a) than empirically observed (for similar results for other linguistic constructions, obtained using the maze task, see Wilcox et al 2021). Such substantial underestimation of processing difficulty by surprisal may indicate that additional processes, such as syntactic reanalysis (Fodor and Ferreira, 1998;Paape and Vasishth, 2022), are recruited during the comprehension of syntactically complex sentences.…”
Section: Introductionmentioning
confidence: 84%
“…They showed that while surprisal correctly predicted that reading times on the boldfaced words in (1a) are longer than the reading times on the same words in (1b), it predicted a much smaller excess processing difficulty on (1a) than empirically observed (for similar results for other linguistic constructions, obtained using the maze task, see Wilcox et al 2021). Such substantial underestimation of processing difficulty by surprisal may indicate that additional processes, such as syntactic reanalysis (Fodor and Ferreira, 1998;Paape and Vasishth, 2022), are recruited during the comprehension of syntactically complex sentences.…”
Section: Introductionmentioning
confidence: 84%